Unfolding the Landscape of Conflict - Made Selly Dwi Suryanti; M. Zaenul Muttaqin; Sukron Makmun (Journal of Southeast Asian Human Rights, 2023)
This study aims to examine the role of the United Nations Fund for Women (UNIFEM) in upholding women's rights by helping victims of sexual violence in the Darfur region of Sudan. By extension, it explores whether the organisation provided an effective example of a feminist groups in the face of this issue. This research is descriptive, using qualitative methods. The data taken is based on relevant books, academic journals, and online material. The analytical tools used are the concepts of feminism and international cooperation. The results of this research show that, when attempting to solve the problem of sexual violence in Darfur, UNIFEM came to the aid of victims, collaborating with local institutions in the area. This resulted in positive outcomes for sexual violence victims in Darfur, though UNIFEM continues to face several challenges. Keywords: Feminism, Sexual Violence, Conflict, UNIFEM